Equal Protection for Children of Same-Sex Parents - Catherine E. Smith (Washington University Law Review, 2013)
Gay rights litigation and advocacy traditionally have focused on the unequal treatment of gay and lesbian individuals and couples; less attention has been dedicated explicitly to the legal rights of the children of gay and lesbian parents. This Article asserts that a child of same-sex parents denied a government benefit has a cognizable equal protection challenge—a legal claim that is separate and distinct from that of the child’s gay or lesbian parents. It is well-settled equal protection law that the government may not treat nonmarital children differently than marital children because of moral disdain for their parents’ relationship, and laws classifying children based on their parents’ marital status are subject to intermediate scrutiny. Today, a majority of states exclude children of same-sex parents from the economic benefits that could be derived from their non-biological same-sex parent, including health insurance, workers’ compensation benefits, child support, and social security benefits. When medical events, divorces, lay-offs or death occur in the lives of children of same-sex parents in these “no-protection” states, they are denied important economic safety nets—safety nets that children of married and unmarried opposite-sex parents enjoy. As a subset of nonmarital children, children of same-sex parents exercise no control over their parents’ conduct, but suffer concrete economic injuries because of the state’s imputation of immorality to them. This government-sponsored discrimination cannot be fairly justified on the basis of preserving traditional family values or on the basis of ensuring administrative efficiency. “No-protection” states must dismantle the insurmountable barrier that blocks children of same-sex parents from establishing a legal relationship with their non-biological same-sex parent, and place them on equal footing with their opposite-sex parented peers.
Keywords: same-sex parents; homosexual; government benefit; gay; lesbian